File Hiding Application On Digital Images With Five Modulus Method - Roby Alfian; Arpan; Sri Wahyuni (Sean Institute, 2021)
Steganography is an art and study of invisible communication from confidential data on a multimedia carrier such as image, audio and video files. The most popular steganography method is the LSB (Least Significant Bit) method. However, the LSB method is very vulnerable to attack using basic image processing operations. In 2013, Jassim applied the Five Modulus method in the steganography process. The Five Modulus method will solve a digital image into a set of image subblocks called n x n sizes. Secret messages will be inserted in the window. According to Jassim, the smaller the window size, the more secret messages can be inserted into the image. The resulting steganography software can hide confidential data into a digital image. Secret data stored in the stego image can be extracted out in the extraction process